2020
DOI: 10.1039/d0tb01373k
|View full text |Cite|
|
Sign up to set email alerts
|

A tumor-microenvironment fully responsive nano-platform for MRI-guided photodynamic and photothermal synergistic therapy

Abstract: Multifunctional intelligent theranostics agents are promising for next-generation oncotherapy. We fabricated a tumor-microenvironment (TME)-responsive carbon nanotubes (CNTs)-based nanoplatform with T1 weighted magnetic resonance imaging (MRI)-guided synergistic photodynamic and photothermal therapy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…[13] Furthermore, their ability to get dissociated into nontoxic Mn 2+ ions in the presence of H 2 O 2 and GSH, can enhance their biological clearance and avoid non-specific systemic toxicity. [14] Previous studies have reported the photothermal properties of MnO 2 based nanoparticles. [15,16] Jin Liu et al, has developed enzymatically synthesized MnO 2 nanoparticles for photothermal therapy as well MRI imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Furthermore, their ability to get dissociated into nontoxic Mn 2+ ions in the presence of H 2 O 2 and GSH, can enhance their biological clearance and avoid non-specific systemic toxicity. [14] Previous studies have reported the photothermal properties of MnO 2 based nanoparticles. [15,16] Jin Liu et al, has developed enzymatically synthesized MnO 2 nanoparticles for photothermal therapy as well MRI imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, oxygen-dependent PDT was severely discouraged due to the low intratumoral oxygen level [ 100 102 ]. Fortunately, nanozymes with catalase-like activities could provide a feasible method to improve tumor oxygen-involved therapeutic methods [ 103 , 104 ]. Based on the catalase-like activity, platinum (Pt) based nanomaterials have been widely applied to decompose the endogenous H 2 O 2 to O 2 , thus relieving tumor hypoxia for tumor therapy, including PDT and radiotherapy [ 105 , 106 ].…”
Section: Platinum-based Nanozymesmentioning
confidence: 99%
“…Wang et al . constructed MWNTs-based nanosystem for MRI-guided and TME-responsive phototherapy [ 139 ]. A uniform MnO 2 layer and photosensitizer Ce6 were modified on MWNTs for enhanced phototherapy.…”
Section: Carbon Nanotubes In Cancer Treatmentmentioning
confidence: 99%